Comparative analysis of virus-host interactions caused by a virulent and an attenuated duck hepatitis A virus genotype 1 - Ou, Xumin (PLoS One, 2017)
Because of their better immunogenicity and the improved protection they afford, live attenuated vaccines derived from serial passaging in an abnormal host are widely used to protect humans or animals from certain pathogens. Here, we used a virulent and a chicken embryo-attenuated duck hepatitis A virus genotype 1 to compare the different regulated immune responses induced by viruses with differing virulence. In this study, the attenuated strains had lower protein expression levels than the virulent strains as identified by immunohistochemistry. This may be caused by apparent codon usage bias selected during passage. Furthermore, lower translation efficiency led to decreased viral replication, which is highly dependent on non-structural viral protein expression. Although the two strains had differing levels of virulence, both could induce strong innate immune responses and robust Tc or Th cell populations during the early stages of the immune response. However, due to fixed single nucleotide polymorphisms (SNPs) selected by passage, the virulent and attenuated strains may induce differing immune responses, with stronger Tc cell immunity induced by the attenuated strain in the spleen and thymus and stronger Tc cell immunity induced by the virulent strain in the liver, lung, bursa of Fabricius and Harderian gland. Four immune related genes (RIG-1, MDA5, IFN-β, and IL-6) were highly differentially expressed in the Harderian gland, bursa of Fabricius and thymus. This study has provided further information about differences in virus-host interactions between duck hepatitis A viruses of differing virulence.